Learning Theology by using Meurukon as The Media - Mohd. Harun; Siti Sarah Fitriani; Nurrahmah Nurrahmah (Balai Bahasa Provinsi Bali, 2026)
Meurukon is a well-known Islamic art in an Acehnese society that live in the northernmost of Sumatera Island, Indonesia. Very little research has raised meurukon as the research subject to analyze its theological elements. This study aims at describing the theology in Meurukon and the use of Meurukon as a medium for learning theology. This qualitative research gathered data by collecting Meurukon manuscripts from Rahman (2010) and Huda (2018), and interviewing eight informants. The results showed that the main theological issues discussed in Meurukon are the nature of religion and the nature of God, faith, Islam, classification of Allah’s 20 attributes, faith in angels, doomsday sign, the foundation of prayer, and the Apostle's command. The analysis has also found that Meurukon as a medium for learning theology is used through compulsory activities in pesantren (Islamic boarding schools), extracurricular activities in schools, routine activities in celebrating religious holidays, competitions between villages, districts, and cities, broadcasts on television media, rice harvest parties, and teaching materials or courses at literary and art universities. AbstrakMeurukon merupakan salah satu kesenian Islam yang dikenal luas dalam masyarakat Aceh yang mendiami wilayah paling utara Pulau Sumatra, Indonesia. Sangat sedikit penelitian yang mengangkat meurukon sebagai objek kajian untuk menganalisis unsur-unsur teologis yang terkandung di dalamnya. Penelitian ini bertujuan untuk mendeskripsikan aspek-aspek teologi dalam meurukon serta pemanfaatan meurukon sebagai media pembelajaran teologi. Penelitian kualitatif ini mengumpulkan data melalui pengkajian naskah-naskah meurukon yang dihimpun oleh Rahman (2010) dan Huda (2018), serta wawancara dengan delapan informan. Hasil penelitian menunjukkan bahwa persoalan-persoalan teologis utama yang dibahas dalam meurukon meliputi hakikat agama dan hakikat Tuhan, iman, Islam, klasifikasi dua puluh sifat Allah, iman kepada malaikat, tanda-tanda hari kiamat, dasar-dasar salat, serta perintah-perintah Rasul. Analisis juga menemukan bahwa meurukon sebagai media pembelajaran teologi dimanfaatkan melalui kegiatan wajib di pesantren, kegiatan ekstrakurikuler di sekolah, kegiatan rutin dalam peringatan hari-hari besar keagamaan, perlombaan antardesa, antarkecamatan, dan antarkota, siaran di media televisi, pesta panen padi, serta sebagai bahan ajar atau mata kuliah di perguruan tinggi bidang sastra dan seni.